Twitter Sentiment Analysis Towards Qatar as Host of the 2022 World Cup Using Textblob - Syarafina Dewi; Dede Brahma Arianto (International Journal Labs, 2023)
Twitter provides services to its users in the form of creating status messages or what is usually called tweets. Through tweets users can express opinions, views, or emotions towards a topic. On 2 December 2010, Qatar was selected to host the 2022 World Cup. Qatar's selection as the host of the 2022 World Cup could elicit a variety of responses from various circles around the world. This research used Textblob to find out the sentiment of Twitter users around the world regarding Qatar as the host of the 2022 World Cup. This research is divided into 3 stages, namely before the selection of Qatar as the host, after the selection of Qatar as the host, and when the 2022 World Cup takes place in Qatar. The results of the study resulted in positive sentiment as much as 84% and negative sentiment as much as 16%. Based on the study, an accuracy score of 0.87 or 87% was obtained, meaning that the model was able to accurately predict 87% of the total testing data. This study can predict new data without having to be labeled first.